Pengaruh Ekstrak Kulit Bawang Merah Terhadap Daya Hambat Bakteri Aeromonas hidrophilla Penyebab Penyakit Pada Ikan Secara In Vitro - Andi Welly Wiliandhana Pranata; Ida Bagus Jelantik Swasta; Gede Iwan Setiabudi (Universitas Bangka Belitung, 2025)
Aeromonas hydrophila, commonly found in aquatic environments, is a Gram-negative bacterium frequently pathogenic to fish, causing diseases such as hemorrhagic septicemia or Motile Aeromonas Septicemia (MAS) in various freshwater fish species. This study investigated the antibacterial potential of red onion skin extract (Allium cepa L.) extracted using 99% absolute alcohol against the growth of Aeromonas hydrophila. The experiments were conducted with varying extract concentrations of 5%, 10%, 15%, 20%, and 25%, using tetracycline as a control. The results demonstrated that the red onion skin extract was able to inhibit the growth of Aeromonas hydrophila, as indicated by the formation of inhibition zones around the growth media. The average diameters of the inhibition zones produced by the extract at concentrations of 5%, 10%, 15%, 20%, and 25% were 1.21 mm, 2.43 mm, 3.36 mm, 5.70 mm, and 6.23 mm, respectively. Statistical analysis using a One-way ANOVA test with SPSS software showed a p-value of 0.000, indicating a significant difference among the red onion skin extract concentrations. Therefore, a Least Significant Difference (LSD) post-hoc test was performed to identify specific differences between the concentration treatments